Documentation FiFoSiM: integrated tax benefit microsimulation and CGE model - Thilo Schaefer; Andreas Peichl (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2006)
This documentation describes FiFoSiM, the integrated tax benefit microsimulation and CGE model of the Center of Public Economics at the University of Cologne. FiFoSiM consists of three main parts. The first part is a static tax benefit microsimulation module. The second part adds a behavioural component to the model: an econometricaly estimated labour supply model. The third module is a CGE model which allows the user of FiFoSiM to assess the global economic effects of policy measures. Two specific features distinguish FiFoSiM from other tax benefit models. First, the simultaneous use of two databases for the tax benefit module and second, the linkage of the tax benefit model to a CGE model.
Keywords: D58; J22; H2; 330; FiFoSiM; microsimulation; CGE; Steuersystem; Sozialtransfer; Allgemeines Gleichgewicht; Simulation; Arbeitsangebot; Beschäftigungseffekt; Wirtschaftswachstum; Theorie; Mikrosimulation